An enhanced immunochromatography assay based on colloidal gold-decorated polydopamine for rapid and sensitive determination of gentamicin in animal-derived food. (1st September 2022) - Pang, Yimeng; Zhao, Sijun; Liu, Zhiwei; Chen, Jiayi; Yang, Zehao; He, Zixian; Shen, Xing; Lei, Hongtao; Li, Xiangmei
Highlights: The CG@PDA-ICA was firstly developed to detect GEN in animal-derived food. The LOD of CG@PDA-ICA was up to 92-fold more sensitive than the reported CG-ICA. CG@PDA was synthesized with better signal intensity and colloidal stability than CG. Abstract: In this study, an enhancing immunochromatography assay (ICA) based on colloidal gold-decorated polydopamine (CG@PDA) was firstly developed for gentamicin in milk, muscle, liver and kidney simultaneously. CG@PDA was synthesized by one-pot method with better signal intensity, colloidal stability, and antibody coupling efficiency than traditional colloidal gold. The detection limit of the developed ICA was about 1.50 μg/kg for the four animal-derived food, which was up to 92-fold more sensitive than the reported ICA based on colloidal gold. The recovery rates were ranged from 86.0% to 114.0% with coefficient of variation between 1.6% and 13.1%. Parallel analysis of 40 samples by commercial ELISA kits was confirmed the reliability. Our research indicated that polydopamine decorated can chemically modify the surface of colloidal gold and can thus remarkably improve the detection performances of ICA.